The Effect of General Allocation Funds, Economic Growth, and Area on The Level of Financial Independence of The Provincial Government Regions in Indonesia - Sulangi, Praisy Gratia; Anwar, Choirul; Ulupui, I Gusti Ketut Agung (Jurnal Akuntansi, Perpajakan dan Auditing, 2022)
This study aims to analyze and examine the effect of the General Allocation Fund, economic growth, and area of the region on regional financial independence. The population on this study was all provinces in Indonesia. The sample was selected using a purposive sampling method so that a sample of 31 provinces was selected which resulted in 62 observations with a 2-year research period, 2018-2019. Data were analyzed using multiple linear regression analysis. The resultsof this study indicate that the General Allocation Fund has a positive effect on regional financial independence, while economic growth has no effect on regional financial independence and area size has a negative effect on regional financial independence. The independent variables of the General Allocation Fund, economic growth, and the area of the region can explain the dependent variable, namely regional financial independence through a determination coefficient of 12.2%